Pseudocyst of Abdomen Presenting as a Huge Abdominal Mass after Ventriculoperitoneal Shunt: A Case Report - Adhikari, Suman; Bhandari, Prabin; Karmacharya, Balgopal; Yogi, Nikunja (Journal of Advances in Internal Medicine, 2021)
A ventriculoperitoneal shunt is a major surgical modality to relieve intracranial pressure in patients with hydrocephalus. Shunt obstruction and infection are the most common complications following shunt surgery whereas VP shunt-associated pseudocyst formation is a rare complication. These are the cystic space without the epithelial lining, filled with fluid around the distal tip of the catheter. In this case report, we present you a 47-year-old male who underwent VP shunt placed a year back presented with huge abdominal swelling, headache, and weight loss. CT scan of the abdomen showed abdominal pseudocyst with the peritoneal end of the shunt within the cyst. Though the exact mechanism is not known, abdominal adhesion, multiple revisions, obstruction, or dislodgement are thought to predispose to the formation of a pseudocyst.